Flame atomic absorption spectrometry combined with surface-modified magnetic mesoporous silica microspheres by polyethyleneimine for enrichment, isolation and determination of Cu2+ in preserved eggs after high-temperature digestion. Issue 11 (2nd November 2022) - Li, Zhengxiang; Che, Tong; Yang, Minghong; Hu, Xujia
Abstract: A new efficient magnetic solid-phase extractant based on a surface-modified magnetic mesoporous silica microsphere referred as MMSM-PEI was synthesised and used for the enrichment and isolation of copper ions (Cu 2+ ) in preserved eggs. The physicochemical properties and morphology of MMSM-PEI were characterized by X-ray diffraction (XRD) spectroscopy, Fourier transform infrared spectroscopy (FT-IR), vibration sample magnetometry (VSM), scanning electron microscopy (SEM) and thermos-gravimetric analyses (TGA). The concentrations of trace Cu 2+ in the preserved egg were determined by flame atomic absorption spectroscopy (FAAS). The effects of important parameters were examined. The most suitable pH values and temperature for adsorbing Cu 2+ were 6.5 and 25 °C, respectively. According to the determination of Cu 2+ in egg white, egg yolk and the outer coating mixture (TOCM) of preserved eggs, the spiked recovery and RSD were 94.1–103.8% and 0.96–4.35%, respectively. The limit of detection (LOD) and the limit of quantitation (LOQ) were 0.14 mg/kg and 0.46 mg/kg, respectively. The developed method improved the sensitivity and accuracy of FAAS for the determination of Cu 2+ and it could be applied to the determination of trace Cu 2+ in real samples.